(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This article analyzes the historical and spiritual heritage associated with the Termez Sayyid dynasty and local architectural traditions, using the example of the Sultan Saodat architectural complex in the Surkhandarya region. The author examines the architectural features of the mausoleums, construction techniques, decorative elements, and how they reflect cultural and religious values. In particular, the complex, which developed gradually between the 11th and 17th centuries, is described as a compact composition comprising several mausoleums, a mosque, and a khanaqah. The article also presents information about Sayyid Hasan al-Amir and his descendants based on genealogical sources. Furthermore, it explores the historical origins of the Termez Sayyids, their possible connections to the Samanids, and the functioning of the local naqib institution. Special attention is given to the fact that the Sultan Saodat complex was preserved through the initiative of the local population during the Soviet era, a time when efforts were made to destroy Islamic monuments. This study holds significant value from the perspective of local history, Islamic architecture, and the restoration of national cultural heritage.